Utilizing available time-varying operating condition information in learning-based methods for fault diagnostics of rotating machinery - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2023)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2022.